PERAN KAUM DEWASA DALAM MENINGKATKAN KERASULAN DI BIDANG POLITIK BAGI KAUM MUDA DALAM TERANG DEKRIT APOSTOLICAM ACTUOSITATEM 12 - Ola Rongan Wilhelmus; Yuvinus Sujiman (Lembaga Penelitian STKIP Widya Yuwana, 2018)
Participation in politics is the rights and obligations of citizens. The Church and the Government has been providing a wide range of container construction for young people. This aims to help young people become responsible individuals, including in the exercise of their rights and obligations in the field of politics. The Second Vatican Council Decree Apostolicam Actuositatem through article 12 confirms that adults play a role built dialogue, give example and wise advice, andencourage young people to the apostolate, including in the field of politics. The outline of the research issues include: what does political and Ministry, whether politics is part of the Apostolic Church, how young people's interest and involvement in the political sphere, and how implementation of the role of adults in improving the Ministry in the field of politics for young people based on the mandate of the Decree Apostolicam Actuositatem article 12. Based on the outline of the issue, this research aims to describe the sense of politics and Ministry, describing politics as part of the Church's apostolic work, analyzing the interest and involvement of young people in the political sphere, and analyze the implementation role of adults in improving the Ministry in the field of politics for young people. The research was carried out in may 2015 in the parish of St. Cornelius Parish and Mater Dei of Madiun. The researchers used a qualitative research method. The respondents of the research consisted of six young people and four adults. The process of collecting data using the method of interview. The results showed that politics is an attempt to achieve common prosperity. And Ministry is an attempt to achieve a common prosperity based on the teachings of the Church. Politics is part of the Apostolic Church. However, young people are less interested and involved in political activities. In addition, adults have not been able to carry out their task in improving the Ministry in the field of politics for young people effectively and optimally.